Match performance of football teams in different competition phases: Analysis on the data of eight consecutive seasons in the Chinese Super League - Li, Pei; Zhong, Shisheng; Chmura, Paweł; Liu, Hongyou (Frontiers in Psychology, 2023)
The study aims to quantify the variation in the physical and technical match performance of football teams in different months of a season in the Chinese Super League (CSL). Data of 1899 matches in the seasons 2012-2019 of CSL collected by Amisco Pro® were analysed. The generalised mixed modelling was employed to estimate the per match mean values of 6 physical performance-related parameters and 16 technical performance-related parameters of CSL teams in every month of all the 8 seasons. Results showed that: (1) the mean values of all the analysed physical performance-related parameters (total/sprint/HSR/MSR distance, sprint/HSR efforts) of CSL teams through a season were characterised like a "U" shape, the highest value was observed in the beginning of season (March), then decreased gradually, reaching the lowest in August, and rebounded progressively from September to November; (2) the mean values of 8 technical performance-related parameters (goals, shots, shot accuracy, individual possession, individual possession in the last third, crosses, cross accuracy, and yellow cards) presented trivial changes through the whole season; (3) the number of passes, passes per shot, forward passes, and time in individual possession showed trivial changes from March to October, but showed a substantially increase in November (the last month of season); (4) Pass accuracy, forward pass accuracy, and the number of mean ball touches per individual possession substantially increased in June, July and August, while the number of challenges, ground challenges, air challenges, tackles and fouls all substantially decreased in these three months. These results could provide detailed information to help the practitioners in the periodization of training and match preparation.